2020
DOI: 10.3390/en13030589
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Noise Induced by Unstable Flow in a Centrifugal Pump

Abstract: In order to investigate the mechanism and the characteristics of the noise induced by unstable flow in a centrifugal pump, the internal flow characteristics in the pump were numerically researched, and the acoustic pressure fluctuations at the pump inlet and outlet were experimentally investigated. Obvious corresponding relationships between the flow instabilities, the cavitation and the noise were established. It was found that the rotating stall, the backflow, the hump, the occurrence of unstable flow and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Cheng et al [10] improved the noise of a centrifugal pump by cutting the outlet side of the impeller, and found that there exists an optimal cutting width to weaken the rotorstator interaction between the impeller and the volute, which effectively reduces its internal and external sound field. To study the mechanism of noise induced by unstable flow inside a centrifugal pump, Lu et al [11] analyzed it through a combination of experiments and numerical simulations and found that the noise could effectively react to the phenomena of flow stall and instability inside the pumps. Paramasivam et al [12] through studying the effect of guide vanes on centrifugal fans found that centrifugal fans with conical guide vanes radiated lower noise sound pressure levels as compared to the original model.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [10] improved the noise of a centrifugal pump by cutting the outlet side of the impeller, and found that there exists an optimal cutting width to weaken the rotorstator interaction between the impeller and the volute, which effectively reduces its internal and external sound field. To study the mechanism of noise induced by unstable flow inside a centrifugal pump, Lu et al [11] analyzed it through a combination of experiments and numerical simulations and found that the noise could effectively react to the phenomena of flow stall and instability inside the pumps. Paramasivam et al [12] through studying the effect of guide vanes on centrifugal fans found that centrifugal fans with conical guide vanes radiated lower noise sound pressure levels as compared to the original model.…”
Section: Introductionmentioning
confidence: 99%
“…In the naval ship, submarine and water conservancy and hydropower engineering industry [1], TLV cavitation and the noise caused by it, especially the cavitation and vibration of hydraulic machinery [2], seriously endanger the safe operation of hydraulic machinery, and have received more and more attention and concern. When cavitation occurs, cavitation noise will significantly reduce the hiding characteristics of underwater targets, and even become an extremely important noise source for the overall underwater targets [3]. Therefore, the study of TLV, cavitation and noise plays a vital role.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was found that the type of stall depends on the number of impeller blades. Lu et al [17] used noise to detect instability such as stall and backflow in the centrifugal pumps and established the relationship between flow instability and noise. Shibata et al [18] found that the vortex at the trailing edge of the diffuser vanes of the multi-stage centrifugal pump hinders the flow of fluid and induces flow separation at the leading edge, and it causes the stall phenomenon.…”
Section: Introductionmentioning
confidence: 99%